Best Answer

L1: y = 1/2*x - 3

Gradient of the line = 1/2

Negative reciprocal of gradient = -1/(1/2) = -2

That is, gradient of perpendicular = -2.

This line goes through (0,3),

(y - 3) = 2*(x - 0)

y - 3 = 2x

y = 2x + 3

L1: y = 1/2*x - 3

Gradient of the line = 1/2

Negative reciprocal of gradient = -1/(1/2) = -2

That is, gradient of perpendicular = -2.

This line goes through (0,3),

(y - 3) = 2*(x - 0)

y - 3 = 2x

y = 2x + 3

L1: y = 1/2*x - 3

Gradient of the line = 1/2

Negative reciprocal of gradient = -1/(1/2) = -2

That is, gradient of perpendicular = -2.

This line goes through (0,3),

(y - 3) = 2*(x - 0)

y - 3 = 2x

y = 2x + 3

L1: y = 1/2*x - 3

Gradient of the line = 1/2

Negative reciprocal of gradient = -1/(1/2) = -2

That is, gradient of perpendicular = -2.

This line goes through (0,3),

(y - 3) = 2*(x - 0)

y - 3 = 2x

y = 2x + 3

Q: How do you name the equation of a line that is perpendicular to y equals 1 half x-3 and goes through the point x equals 0 and y equals 3?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

If -14 is the y intercept then it is: y = -1/13x -14

Known equation: 5x-2y = 3 or y = 5/2x -3/2 Slope of known equation: 5/2 Slope of perpendicular equation: -2/5 Perpendicular equation: y- -4 = -2/5(x-3) => 5y =-2x-14 Perpendicular equation in its general form: 2x+5y+14 = 0

Perpendicular equation: x+2y = 0 Point of intersection: (2, -1) Perpendicular distance: square root of 5

7x-y-28 = 0

Perpendicular slope: -1/4 Perpendicular equation: y-0 = -1/4(x-3) => y = -0.25x+3

Related questions

Slope: -2 Equation: y--1 = -2(x-3) => y = -2x+5

If a line has equation y = mx + c, the perpendicular line has gradient -1/m A line perpendicular to 3x + y = 2 has equation 3y = x + c; the value for c will be determined by a point through which the line must pass.

y = 1/3x+4/3

If -14 is the y intercept then it is: y = -1/13x -14

Known equation: 5x-2y = 3 or y = 5/2x -3/2 Slope of known equation: 5/2 Slope of perpendicular equation: -2/5 Perpendicular equation: y- -4 = -2/5(x-3) => 5y =-2x-14 Perpendicular equation in its general form: 2x+5y+14 = 0

Perpendicular equation: x+2y = 0 Point of intersection: (2, -1) Perpendicular distance: square root of 5

The line "x = 6" will be perpendicular to any line "y = C", where C is any constant. That means that the line which is perpendicular to "x=6" and passes through [-4, 5] will be "y = 5"

3x-4y-6 = 0

7x-y-28 = 0

That depends on the equation that it is perpendicular too which has not been given but both equations will meet each other at right angles.

That would depend on its slope which has not been given.

Perpendicular slope: -1/4 Perpendicular equation: y-0 = -1/4(x-3) => y = -0.25x+3